PENGARUH MOTIVASI BELAJAR, BUDAYA SEKOLAH, DAN GAYA BELAJAR TERHADAP PRESTASI BELAJAR SISWA SMP METTA MAITREYA PEKANBARU - Mailiza Amalia (Program Studi Pendidikan Ekonomi Universitas Riau, 2017)
The study aims to determine the effects of learning motivation, school culture, andlearning styles to students’ achievement at SMP Metta Maitreya Pekanbaru. Thisresearch is using descriptive method with quantitative approach. The population ofthe study were junior high school students at Metta Maitreya Pekanbaru. The wholetotal of students in this school is 167 people with a total sample of 118 peopleselected minimum sampling techniques. Data were obtained from observation andresearch by distributing questionnaires to the respondents. Data were analyzedusing mean scores and statistical analysis with multiple linear regression. Againstthe instrument to test the validity and reliability by using Cronbach alpha formula.The results showed that: (1) a significant difference between learning motivationtowards student achievement with t value 6.302 sig. <0.05. (2) there is a significantrelationship between school culture on student achievement with t value 8.621 sig.<0.05. (3) there is no significant relationship between learning styles to studentachievement with t value 0.772 sig. > 0.05. (4) there is a significant influencebetween learning motivation, school culture, and learning styles to studentsachievement at SMP Metta Maitreya Pekanbaru with regression equation Y = 5.075+ 0,791X1 + 1,105X2 + 0,113X3 + εn. From the results of F value is 65.507 with sig.<0.05 and a large coefficient of influence together amounted to 63.3%. From theseresults, it can be concluded that students' motivation is balanced with the junior highschool policy in implementing the culture of the school in the school learningenvironment and learning styles students that can improve students’ achievement.